The Nexus of Altruistic and Courteous Behaviors on Job Satisfaction and Affective Organizational Commitment among Pharmaceutical Executives - Theophilus Ehidiamen Oamen; Maduabuchi Romanus Ihekoronye (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Prior research in several management disciplines has shown that Altruistic and Courtesy organizational citizenship behavior (OCB) positively enhances Affective organizational commitment (OC) and Job Satisfaction (JS) in employees. The study aims to test the assumption that Altruism and Courtesy OCB positively influence JS and Affective OC among pharmaceutical executives in Nigeria. A cross-sectional questionnaire-based survey with data randomly collected from selected respondents (N=401). The assumptive model was evaluated with structural equation modeling using advanced analysis of composites software (ADANCO). The structural model had an acceptable fit and internal reliability of constructs. Study findings revealed that altruism OCB was not a significant predictor of JS and Affective OC (p>0.05). Courtesy OCB was a significant predictor of JS and Affective OC (p<0.01). Courtesy OCB's influence on OC is partially mediated by JS. Pharmaceutical executives' level of emotional attachment and sense of connection towards their organization improves substantially in a friendly, supportive work environment. The empirical model supports intra-collegial collective performance and productivity instead of focusing on an individual's altruistic tendencies. The study reinforces the team-based sales approach as well as the need to reward altruistic behavior from employees and subordinates.